Long noncoding RNA RMRP upregulation aggravates myocardial ischemia-reperfusion injury by sponging miR-206 to target ATG3 expression - Fei Kong (Biomedicine & Pharmacotherapy, 2019)
Objective: Coronary heart disease is a common cause of death and disability worldwide and mainly results from myocardial ischemia-reperfusion (I/R) injury. This study aimed to elucidate the roles and possible mechanism of long noncoding RNA Component Of Mitochondrial RNA Processing Endoribonuclease (RMRP) in protecting against ischemic myocardial injury. Material and methods: The H9c2 cardiomyocytes were cultured under hypoxia condition to induce myocardial injury. The RMRP expression under hypoxia condition was determined, followed by investigation of the effects of RMRP dysregulation on hypoxia-induced injury in H9c2 cells. In addition, the regulatory relationship between RMRP and miR-206 was detected, and the potential target of miR-206 was identified. Besides, the association of RMRP and activation of PI3K/AKT/mTOR signaling pathway was explored. Furthermore, an in vivo rat model of myocardial I/R injury was established by subjection to 60 min ischemia and subsequently 24 h reperfusion for validation of the role of RMRP in regulating myocardial I/R injury in vivo. Results: The results showed that overexpression of RMRP aggravated hypoxia-induced injury in H9c2 cells. Moreover, miR-206 was negatively regulated by RMRP and overexpression of RMRP aggravated hypoxia injury by downregulation of miR-206. Furthermore, ATG3 was a target of miR-206, and he effects of miR-206 on hypoxia injury were through targeting ATG3. Besides, overexpression of RMRP activated PI3K/AKT/mTOR pathway in hypoxia-treated H9c2 cells, which were reversed by miR-206 overexpression at the same time. Furthermore, in an in vivo rat model of myocardial I/R injury, suppression of RMPR improved cardiac function and inhibited apoptosis after myocardial I/R injury. Conclusions: Our findings reveal that upregulation of RMRP may aggravate myocardial I/R injury possible by downregulation of miR-206 and subsequently upregulation of ATG3. Activation of PI3K/Akt/mTOR pathway may be a key downstream mechanism mediating the cardioprotection of RMPR/miR-206/ATG3 axis against myocardial I/R injury.